Autophagy-Related Pathways in Vesicular Unconventional Protein Secretion - Noh, Shin Hye; Kim, Ye Jin; Lee, Min Goo (Frontiers in Cell and Developmental Biology, 2022)
Cellular proteins directed to the plasma membrane or released into the extracellular space can undergo a number of different pathways. Whereas the molecular mechanisms that underlie conventional ER-to-Golgi trafficking are well established, those associated with the unconventional protein secretion (UPS) pathways remain largely elusive. A pathway with an emerging role in UPS is autophagy. Although originally known as a degradative process for maintaining intracellular homeostasis, recent studies suggest that autophagy has diverse biological roles besides its disposal function and that it is mechanistically involved in the UPS of various secretory cargos including both leaderless soluble and Golgi-bypassing transmembrane proteins. Here, we summarize current knowledge of the autophagy-related UPS pathways, describing and comparing diverse features in the autophagy-related UPS cargos and autophagy machineries utilized in UPS. Additionally, we also suggest potential directions that further research in this field can take.